Technology and inclusion - Past, present and foreseeable future. - Bühler, Christian; Engelen, Jan; Emiliani, Pier Luigi; Stephanidis, Constantine; Vanderheiden, Gregg (Technology & Disability, 2011)
The paper considers the Information and Communication Technology sector to discuss some general characteristics of the activities meant to favour inclusion through the use of technology, as well as of the attitudes of actors in this sector. The paper does not claim to give a comprehensive description of the technological applications in the field of eInclusion. Rather, it focuses on a set of examples, reviews some lines of development, and uses these to explore the present situation and potential developments in the near future. Observations include: (i) technology has been very useful to improve the situation of people with activity limitations (AT); (ii) interesting new improvements are possible using available and emerging technologies (improvement of present AT and new products, services and applications); (iii) however, innovation is not very well served due to internal problems in the field; (iv) Design for All could be very useful, but there are business difficulties for its deployment; (v) despite this, many mainstream developers are moving in the direction of producing new products and living environments that will be more usable by people with activity limitations and facilitate their inclusion.